CORRELATION BETWEEN THE RATIONAL AND IRRATIONAL AS AN ASPECT OF THE TRANSITION FROM POTENTIAL INFORMATION TO ACTUAL SOCIAL INFORMATION (Revista Inclusiones, 2020)
The author outlines the correlation of the rational and irrational in public consciousness as a model of the transition from potential information to actual social information. This model consists of the following elements: the rational as a social predicate, and the irrational as visibility (a socio-semantic unity). The operator “metamorphosis” serves as a transition means from the model elements to actual phenomena and vise versa. Other elements of the model are the subject of social activity, as well as the social needs and social invariants of the subject. The subject and its social needs serve as a source for revealing the origin of the rational and irrational, while social invariants serve as a regulator of their correlation. The outcome of the conducted by he author prolific sociological survey validates his theoretical provisions and proves them to be of explicit social significance.